2023
DOI: 10.1111/cen.14885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carnitine on glucose and lipid metabolic profiles and fertility outcomes in women with polycystic ovary syndrome: A systematic review and meta‐analysis

Abstract: Objectives To quantify the effect of carnitine on glucose and lipid metabolic profiles and fertility outcomes in women with Polycystic ovary syndrome (PCOS). Design A systematic review and meta‐analysis were conducted. Patients Women with PCOS diagnosed by Rotterdam or Androgen Excess Society (AES) criteria and taking carnitine supplement were assessment. Measurements Fertility outcomes (ovulation, clinical pregnancy, live birth, and miscarriage), lipid parameters (BMI, triglyceride, total cholesterol, high‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been reported that carnitines improve ovulation, clinical pregnancy, insulin resistance, and body mass index (BMI) in infertile women with PCOS along with having positive effects on serum lipid profile. Nevertheless, low to moderate certainty of evidence about these effects is reported [ 15 , 16 , 17 ], thereby stimulating further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that carnitines improve ovulation, clinical pregnancy, insulin resistance, and body mass index (BMI) in infertile women with PCOS along with having positive effects on serum lipid profile. Nevertheless, low to moderate certainty of evidence about these effects is reported [ 15 , 16 , 17 ], thereby stimulating further investigation.…”
Section: Introductionmentioning
confidence: 99%